2012
DOI: 10.1519/jsc.0b013e318239f84f
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness of Elite Belgian Soccer Players by Player Position

Abstract: The purpose of this study was to gain an insight into the physical and physiological profile of elite Belgian soccer players with specific regard to the player's position on the field. The sample consisted of 289 adult players from 6 different first division teams. The players were divided into 5 subgroups (goalkeepers, center backs, full backs, midfielders, and strikers) according to their self-reported best position on the field. The subjects performed anaerobic (10-m sprint, 5 × 10-m shuttle run [SR], squat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
103
4
21

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 13 publications
12
103
4
21
Order By: Relevance
“…These findings were similar to findings obtained by Rampinini et al (2010). Boone et al (2012) obtained that fullbacks and midfielders had higher VO2max values (61,2 ± 2,7 ml/kg/min; 60,4 ±2,8 ml/kg/min, respectively) than VO2max values of strikers (56,8 ± 3,1 ml/kg/min) centerbacks (55,6 ± 3,5 ml/kg/min) and goalkeepers (52,1 ± 5 ml/kg/min). The fullbacks and midfielders performed many efforts for positional roles as winning ball and tackling during match.…”
Section: Dupont Et Al (2010) Determined Oxygen Uptake Kinetics By Mosupporting
confidence: 91%
See 1 more Smart Citation
“…These findings were similar to findings obtained by Rampinini et al (2010). Boone et al (2012) obtained that fullbacks and midfielders had higher VO2max values (61,2 ± 2,7 ml/kg/min; 60,4 ±2,8 ml/kg/min, respectively) than VO2max values of strikers (56,8 ± 3,1 ml/kg/min) centerbacks (55,6 ± 3,5 ml/kg/min) and goalkeepers (52,1 ± 5 ml/kg/min). The fullbacks and midfielders performed many efforts for positional roles as winning ball and tackling during match.…”
Section: Dupont Et Al (2010) Determined Oxygen Uptake Kinetics By Mosupporting
confidence: 91%
“…In terms of ta-95%VO2max values, findings of our study didn't report any significiant differences among playing positions without significiant difference between goalkeepers and centerbacks. In this regard, our study didn't agree with study of Boone et al (2012).…”
Section: Dupont Et Al (2010) Determined Oxygen Uptake Kinetics By Mocontrasting
confidence: 89%
“…[10][11][12][13][14][15] Davis et al 10 concluded that forwards were the fastest players, ahead of defenders, midfielders, and goalkeepers. Boone et al 11 reported differences in speed and countermovement jump (CMJ) according to playing position. Sporis et al 12 found differences in speed but not for CMJ, while Taskin 13 found no speed differences as a function of position.…”
mentioning
confidence: 99%
“…Haughen, Tønnessen, and Seiler (2013) report significantly lower performance in countermovement jump (CMJ) test in midfielders by 5-6% compared to goalkeepers, forwards and defenders. Similarly, Boone, Vaeyens, Steyaert, Bossche, and Bourgois (2012) present significantly lower jump height in CMJ test in midfielders and full backs in comparison to goalkeepers, midfielders and forwards.…”
Section: Introductionmentioning
confidence: 77%